What is a Foreign Firm? Implications for Productivity Spillovers - Sara L. MacGaughey; Pascalis Raimondos-Møller; Lisbeth Funding La Cour (Center for Economic Studies and ifo Institute (CESifo), 2018)
When searching for productivity spillovers from foreign firms, a firm is typically classified as foreign using a low threshold of direct foreign ownership. Instead, we advocate an `ultimate owner' definition because (i) ultimate ownership includes indirect ownership links that are prevalent in our complex, interdependent world; and (ii) it confers control. Control brings greater willingness to transfer knowledge to foreign affiliates but, paradoxically, also greater potential for spillovers. Adopting this alternate definition of what is foreign turns out to be pivotal for identifying spillovers: while we find no horizontal productivity effects using the low threshold direct ownership definition, we find positive and significant effects under the ultimate-owner definition. Moreover, we find evidence that indirectly controlled foreign firms exert the most persistent horizontal spillovers to domestic firms.
Keywords: F21; 330; foreign direct investment; direct vs. ultimate owner; indirect ownership links; control vs. influence; productivity spillovers